(untitled) (AYUSHDHARA, 2020)
Ayurveda deals with the Dravya, Guna and Karma of helpful and harmful materials (...yatascha aayushyyaani anaayushyani cha dravyagunakarma ani vedayatyato apyaayurvedaha….). It is not possible to speak about everything every time but one should decide their specific and own application as per necessities and should determine appropriately. The entities which are not much important and unavailable and if unavailable are not discussed it remains Anukta. Need of Anukta aushadi dravya is important because there is no material which cannot be used as drug (Jagat evam anoushadam). Anukta literally means unsaid, unuttered. In the context where nothing is clearly said, Anukta is taken as standard parameter. It helps not only in understanding the classical concepts but also becomes base for understanding the new diseases, drugs and treatment principles and so on. Problem facing related to Anukta dravya is Pratyaksham hi alpam, apratyaksham hi analpam i.e., known is less, unkown is more. Problem facing is difficulty in assessment of new drug in all aspects Naama, Rupa, Guna, Karma, Prayoga. Already we find scattered references regarding guidelines to know Anukta dravya based on classical text mainly according to Charaka. So this proper perception fulfils the scarcity of classical references to know the Anukta dravya, which in turn may help to take a clinical research based on this literary research.